In-situ Al3Ti particle reinforcement for stiff aluminum die castings - Himmler, David; Randelzhofer, Peter; Körner, Carolin (Journal of Alloys and Compounds, 2022)
The intermetallic phase Al3Ti is a promising candidate to increase the stiffness of aluminium casting alloys due to its high Young’s modulus. Reinforcement particles are formed by the in-situ reaction between solid titanium particles and the liquid aluminium melt. A high-shear mixer is used to peel off the reaction layer on the surface of the Ti particles and distribute the Al3Ti particles homogeneously in the melt. This work investigates the dissolution velocity of different size fractions of Ti powder in three different aluminum casting alloys. The results were used to fabricate specimens with different volume fractions of Al3Ti particles by high pressure die casting. Microstructure characterization was performed to investigate the distribution of the Al3Ti particles within the castings. The mechanical properties were determined by tensile tests and resonant frequency analysis.
Keywords: metal matrix composites; liquid-solid reactions; mechanical properties